2022
DOI: 10.1007/s41669-022-00353-3
|View full text |Cite
|
Sign up to set email alerts
|

An EQ-5D-5L Value Set for Belgium

Abstract: Objective This study aimed to establish a Belgian EQ-5D-5L value set based on the preferences of the adult Belgian general population. Methods The most recent EuroQol Valuation Technology (EQ-VT 2.1) protocol for EQ-5D-5L valuation studies was followed. Computer-assisted personal interviews were carried out in a representative sample of the adult Belgian population. Potential respondents were randomly selected from the National Register using a multistage, stratified, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The EuroQol-5 Dimension-5 Level questionnaire (EQ-5D-5L) is composed of a descriptive system covering 5 dimensions (ie, mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) defined by 5 severity levels (ie, no problems, slight problems, moderate problems, severe problems, and extreme problems/unable to) from which a single index value or utility value can be calculated, ranging from 0 (death) to 1 (perfect health) and with negative values indicating health states perceived to be worse than death ( 20 ). Recently, an EQ-5D-5L value set was developed according to the health state preferences of the general population of Belgium ( 21 ). Possible index values of this value set range from −0.532 to 1.…”
Section: Methodsmentioning
confidence: 99%
“…The EuroQol-5 Dimension-5 Level questionnaire (EQ-5D-5L) is composed of a descriptive system covering 5 dimensions (ie, mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) defined by 5 severity levels (ie, no problems, slight problems, moderate problems, severe problems, and extreme problems/unable to) from which a single index value or utility value can be calculated, ranging from 0 (death) to 1 (perfect health) and with negative values indicating health states perceived to be worse than death ( 20 ). Recently, an EQ-5D-5L value set was developed according to the health state preferences of the general population of Belgium ( 21 ). Possible index values of this value set range from −0.532 to 1.…”
Section: Methodsmentioning
confidence: 99%
“…3 b). Furthermore, comparing the Belgian general population’s preferences for child and adolescent versus adult health states showed that the Kernel densities of the EQ-5D-5L valuation study for adults [ 12 ] is the same shape and scale and close to the curve of the EQ-5D-Y-3L valuation study (Fig. 3 c), and both are different from the older EQ-5D-3L VAS-based curve [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analyses including and excluding all data collected during the pandemic revealed a minimal impact of these data on the estimates of the value set (average difference of the coefficients of the value set was 0.002). Furthermore, the ranking of the domains remained identical with and without the data collected during the pandemic [ 12 ]. However, a dedicated study on the effect of the COVID-19 pandemic on the attributed VAS values [ 27 ] to the best health state (11111), dead and the worst health state (55555, when using the five-level version of the EQ-5D-5L) indicated that the best health state and dead were valued lower, whereas the worst health state was valued higher post-pandemic compared with before the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations